Bioceramic resonance induced extrasensory perception or altered state of consciousness: A pilot study of Taiwan - Kai Leung, Ting (Chulalongkorn Medical Journal, 2020)
Background: Bioceramic resonance (BR) is a technology already applied to clinical medical services, it may help us gain knowledge on consciousness and cognitive neuroscience. Our knowledge of consciousness is far behind other divisions of neuroscience. Objective: This study aimed to evaluate the effect of BR on perception, state of consciousness, and the related mental activity. Methods: BR was applied on 155 adult subjects of Chinese who lived in Taiwan; they received questionnaire assessment of consciousness change or subjective response before and after using BR system. Further observations of selected cases were conducted for follow-up BR experiment. Precise descriptions and statistical analysis were performed on the results. Results: Through the application of BR, participants (n = 155) reported specific perceptions, which include: (a) improvement in their sleep quality; (b) subjective sensation through certain parts of the skin; (c) deep swirling and light/color visualizations; and, (d) more intriguing cases involved candidates who had inexplicable phenomena with audio-visual experiences, such as rotating ‘mandala’. In this study, we explain how BR affects different candidates with variable extrasensory perception experiences and alters state of consciousness. Conclusions: It is attempted to hypothesize that the BR effect may correlate with Jungian concept and the possibility of instrumentalization on psychotherapy. We conclude that BR is a non-invasive method, with potential benefits to neurological and psychological fields.